Social Networks and Health Inequalities 2022
DOI: 10.1007/978-3-030-97722-1_15
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks and Disability: Access to and Stabilization of Integration into the Primary Labor Market

Abstract: Social science research and official statistics repeatedly point to the poor employment prospects of people with disabilities compared to those without disabilities (Eichhorst et al., 2010, p. 7; WHO, 2011, p. 237; Engels et al., 2017, p. 166 ff.; von Kardorff et al., 2013, p. 7 ff.; Pfaff, 2012, p. 235 ff.; Rauch, 2005, p. 28 ff.). People with disabilities are therefore also less likely to benefit from the manifest and latent functions of employment (Jahoda, 1983). The manifest functions include financial res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…People with disabilities generally experience low levels of social integration and inclusion compared to the general population [7,8] for various reasons, such as functional limitations [9], social stigma, and discrimination [10]. People with disabilities have fewer social contacts and are less likely to begin relationships in everyday life [11], further leading to poorer employment opportunities and health outcomes [12]. Moreover, a study on different social networks among people in Kerala showed that 37.6% of PWDs had a private restricted network type rather than a locally integrated one [13].…”
Section: Social Network Of People With Disabilitiesmentioning
confidence: 99%
“…People with disabilities generally experience low levels of social integration and inclusion compared to the general population [7,8] for various reasons, such as functional limitations [9], social stigma, and discrimination [10]. People with disabilities have fewer social contacts and are less likely to begin relationships in everyday life [11], further leading to poorer employment opportunities and health outcomes [12]. Moreover, a study on different social networks among people in Kerala showed that 37.6% of PWDs had a private restricted network type rather than a locally integrated one [13].…”
Section: Social Network Of People With Disabilitiesmentioning
confidence: 99%